Rationale for determining the types of adaptation to predict in sport - Anatoliy Rovnyy; Viktor Lastochkin (Kharkiv State Academy of Physical Culture, 2015)
Purpose: theoretical and practical study adaptation types beginners. Materials and Methods: an analytical synthesis of scientific literature data, the determination of the concentration of lactic acid testing of motor activity. Results: based on the parameters set lactate types of adaptation: «sprinters», «stayers», «mixed type». Conclusions: the establishment of types of adaptation makes it possible to recommend a special focus budding athletes in the sport